The effects of personality traits on learning engagement among college students: the mediating role of emotion regulation - Dang, Tongtong; Du, Wenxiu; Niu, Menghui; Xu, Zhenguo (Frontiers in Psychology, 2025)
IntroductionAs we all know, learning engagement is a key indicator for measuring the quality of students’ learning outcome and assessing their learning effectiveness. However, the relationship among personality traits, emotion regulation, and learning engagement has not been thoroughly studied.MethodsThis study aims to investigate the relationship among personality traits, emotion regulation and learning engagement. A questionnaire survey was conducted on some college students in Shandong Province, China.ResultsThe results show that: (1) there are no significant differences in Big Five Personality Traits, learning engagement, and emotion regulation by gender, grade level, and subject category to which the major belongs. (2) The personality traits of college students can directly affect learning engagement. (3) Emotion regulation partially mediates the relationship between personality traits and learning engagement.DiscussionThe study reveals the importance of personality traits and emotion regulation on students’ learning. It has a significant meaning in enhancing students’ learning engagement level.